The Results of Using the Phonics Approach to Enhance the Reading Aloud on Thai Words with the Final Consonant of Prathomsuksa 3 Students Using Thai as a Second Language: Case Study of Baan Wanalaung School - Sittikhyo, Preeyasiri; Sattayopat, Sanit; Intun, Sasithorn (Chophayom Journal, 2025)
The objectives of this research were: 1) to study the context and error in the reading aloud on Thai words with the final consonant, 2) to construct the lesson plans through the phonics approach to enhance the reading aloud on Thai words with the final consonant, and 3) to compare the achievement of reading aloud on Thai words with the final consonant between pre-test and post-test results. The population were 13 Prathomsuksa 3 students of Baan Wanalaung School, Pang Ma Pha District, Mae Hong Son Province. in the second semester of the academic year 2022. The researcher proceeded according to the research methodology in 3 phases. The research instruments included: : the interview document exploring the context and error of the reading aloud on Thai words with the final consonant for Thai language teachers, a diagnostic test of the reading aloud on Thai words with the final consonant, lesson plans through the phonics approach to enhance the reading aloud on Thai words with the final consonant, and the learning achievement test of the reading aloud on Thai words with the final consonant. The statistical methods used for quantitative data analysis were frequency, percentage, mean, and standard deviation. Qualitative data were analyzed using content analysis. The finding reveals that: 1) the context and error in the reading aloud on Thai words with the final consonant should involve active learning, instructional media, learning activities, and educational assessment and evaluation aligned with the learners' context and development, within a positive classroom environment. Specific sound deficiencies were identified in pronouncing [d], [b], [n], and [ng] sounds. 2) The quality of the lesson plans through the phonics approach in terms of an overview was rated the highest level (μ=4.89, SD = 0.14). And 3) the achievement of reading aloud on Thai words with the final consonant results were an average pre-test score of 26.62 (52.19 percent) and a post-test score of 39.15 (76.77 percent), The result showed the learning achievement post-test was higher than the pre-test by 24.59 percent. Keywords: phonics approach, reading aloud, Thai words with the final consonant, second language, Lahu language